Typology of realism and Kazakh literary studies - Anissa Beisentai, Zhansaya Zharylgapov, Zhanar Rustemova, Sarzhan Takirov, Sayan Kenzhegaliev, (Opción, 1970)
The article examines the scientific concept of theoretical problems of realism in Kazakh literature. It carries out typological analysis of realism as a method in the theoretical works of Kazakh literature and the works of foreign scientists. The works of individual scholars were analyzed, the object of the research which has become the common understanding of realism as a method. Identifies new research problems philosophical outlook of nature of the Kazakh people. Set connection in the new methodical approaches of Kazakh and Russian literature.